Structural changes of Cr-beidellite treated up to 1350 °C in oxygen or nitrogen atmospheres - Santos, H. S. (2017)
Beidellite clay mineral after intercalation of OH-Cr(III) species were thermally analyzed up to 1350 °C in oxygen and nitrogenatmospheres. OH-Cr-beidellite can be used as a pillared clay precursor for catalysis or as adsorbent applications. However, inthis paper beidellite enriched in chromium were analyzed at different thermal treatments up to high temperature for evaluatingstructural changes for possible future ceramic applications. The structural changes were followed by thermal analysis and X-raydiffraction. The thermal treatment of OH-Cr-beidellite in oxygen and nitrogen atmospheres developed different mineralogicalphases up to 1050 °C, but at higher temperatures, the same phases were developed in both atmosphere treatments. Eskolaitephase (Cr2O3) appeared in the sample after heating at 400 °C in oxygen atmosphere, whereas grimaldite (CrO-OH) in nitrogenatmosphere, maintaining the starting phases. At 1000 °C the raw clay minerals disappeared, as it is knew. At 1050 °C in nitrogenatmosphere, grimaldite was absent and eskolaite appeared. At 1350 °C in the samples calcined in both atmospheres, quartz,cristobalite and mullite as the main phases and in lower contents aluminum oxide and aluminum-chromium oxide [(Al,Cr)2O3]were present.